The Intention to Use Mobile Banking as a Financial Technology Service among Islamic Bank Users - Juwita, Ratna; Kusumah, Adam Darma; Aqila, Tiara Syahrani; Tsabitah, Hanan; Syauqi, Muhammad Farhan (The Indonesian Capital Market Review, 2023)
The development of Financial Technology (FinTech) in Islamic banks has not brought increasing us- ers. Therefore, it is necessary to determine which factors influence intention to use FinTech from the demand side or the customers’ side. For this study, we chose mobile banking as our research object, considering that the largest digital transactions in Islamic banks come from mobile banking. Mobile banking also provides banks various benefits to banks such as increased long-term profitability, cus- tomer loyalty, and financial inclusion. The objective of this study is to observe the determinant factor by using the theory of planned behavior (TPB) and its extensions, specifically attitude awareness, knowledge, and subjective norms that influence the intention to use mobile banking. This study gath- ers data regarding respondents from various generations, especially generations X, Z, and millenni- als. The results suggest that attitude and knowledge statistically have a positive effect, while aware- ness and subjective norms do not have a significant effect on intention to use mobile banking services among Islamic bank users. Islamic banks should better educate their consumers and focus on which factors inspire a positive attitude toward their customers to boost the adoption of mobile banking.